Peningkatan Pemahaman Budaya Sebagai Identitas Bangsa Melalui Makanan dan Minuman pada Generasi Muda - Pradana, Triandi; Tanadi, Leon; Lawrence, Jennifer (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Globalization has introduced foreign cuisines, such as Korean and European food, which often attract more interest from young consumers compared to the variety of Indonesian traditional foods. This phenomenon has led to a decline in the popularity of traditional cuisine among the younger generation. This Community Service activity was conducted at SMK Atisa Dipamkara, located in Binong, Curug District, Tangerang Regency, as part of efforts to strengthen the role of educational institutions in preserving local culture. The primary target of this activity was 10th-grade (class X) students, who are in the early phase ofcharacter, attitude, and value orientation formation as vocational students. The service method was divided into three main stages: preparation, implementation, and evaluation of activities. To measure the success level of this service activity, the service team administered a Post-Test to 35 students. Pre-Tests and Post-Tests are essential instruments for evaluating the effectiveness of a learning intervention, training, or educational program concerning the traditional mixology of traditional cuisine as a cultural heritage. Many students initially viewed Nusantara (Indonesian Archipelago) cuisine merely as everyday food or drink without associating it with identity values, philosophy, or national character. Conversely, the Post-Test results indicated a significant increase in understanding. Students began to explain the role of traditional food and beverages in shaping cultural identity, as well as the importance of innovation to keep Nusantara cuisine relevant amidst globalizations. The benefits of this activity were directly felt by the target community, particularly the 10th-grade vocational high school students, as evidenced by the increased understanding demonstrated by the Pre-Test and Post-Test results. Furthermore, this activity supports the implementation ofthe Pancasila Student Profile Strengthening Project and Work Culture (P5BK) by instilling the values of diversity, nationalism, and appreciation for local wisdom.